2014
DOI: 10.1063/1.4869575
|View full text |Cite
|
Sign up to set email alerts
|

1.7 Gbit/in.2 gray-scale continuous-phase-change femtosecond image storage

Abstract: Articles you may be interested inPhase change behaviors of Zn-doped Ge2Sb2Te5 films Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…The latter can also be achieved through an accumulation of sub-threshold (including fs laser pulse) excitations, facilitating reproducible "greyscale" and neuromorphic switching modes of interest for all-optical data and image processing, and harnessed recently for direct, reversible laser writing of planar optical elements and short/mid-wave IR metamaterials in a chalcogenide thin film. [23][24][25][26] Here, we demonstrate structurally engineered highquality near-infrared transmission and reflection resonances in planar (300 nm thick) dielectric nano-grating metasurfaces of amorphous germanium antimony telluride (Ge 2 Sb 2 Te 5 or GST -a widely used composition in data storage applications), and the non-volatile switching of these resonances via laser-induced crystallization of the chalcogenide. We employ nano-grating array metasurface patterns of subwavelength periodicity ( Fig.…”
mentioning
confidence: 99%
“…The latter can also be achieved through an accumulation of sub-threshold (including fs laser pulse) excitations, facilitating reproducible "greyscale" and neuromorphic switching modes of interest for all-optical data and image processing, and harnessed recently for direct, reversible laser writing of planar optical elements and short/mid-wave IR metamaterials in a chalcogenide thin film. [23][24][25][26] Here, we demonstrate structurally engineered highquality near-infrared transmission and reflection resonances in planar (300 nm thick) dielectric nano-grating metasurfaces of amorphous germanium antimony telluride (Ge 2 Sb 2 Te 5 or GST -a widely used composition in data storage applications), and the non-volatile switching of these resonances via laser-induced crystallization of the chalcogenide. We employ nano-grating array metasurface patterns of subwavelength periodicity ( Fig.…”
mentioning
confidence: 99%
“…When annealed to a temperature between the glass-transition and the melting point, the GST transforms from an amorphous state into a metastable cubic crystalline state, while a short high-density laser pulse melts and quickly quenches the material back to its amorphous phase with a pronounced contrast of dielectric properties observed between the two phases. Although nanosecond and microsecond laser pulses, which provide robust switching between amorphous and crystalline phases, are conventionally used in optical data storage technology, it was recently shown that femtosecond laser pulses can induce multi-level switching 29,30 . In the multi-level regime, metastable semi-crystallized states are created by carefully controlling the energy and the number of stimulating optical pulses.…”
mentioning
confidence: 99%
“…A 730 nm, 75 fs pulse train was reduced to 1 MHz frequency using an electro-optical modulator and focused onto a GST film. To write a pattern in the GST, a low pulse energy was used to heat the film below the melting point but above the glasstransition temperature and thus gradually crystallize it 13 . The size and contrast of crystallized mark can be precisely controlled by selecting the pulse energy and number of pulses used.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…The size and contrast of crystallized mark can be precisely controlled by selecting the pulse energy and number of pulses used. To erase the mark, a single high-energy pulse was applied to have the GST mark melted and cooled rapidly to form the amorphous phase 13 .…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%